An Examination of Developmental Factors in False Confessions. - Gallimore, Madison; Krackow, Elisa (International Journal of Clinical & Experimental Hypnosis)
We examined possible developmental factors associated with false confessions. Participants (N = 33) between 13-and-37-years-old (M = 21.79, SD = 6.20) completed a delay discounting task and a pencil-and-paper measure of impulsivity. A researcher accused the participant of having engaged in an accidental wrongdoing. Approximately half the participants confessed. When chronological age and impulsivity scores of confessors and nonconfessors were examined, neither differed significantly, although Bayesian analyses provided moderate evidence that participants who confessed were older. Additionally, some analyses were conducted by creating developmental groups in which participants were divided into ongoing and completed executive functioning (EF) groups, using age as a proxy for EF. False confessions did not differ by EF-proxy developmental group. However, an analysis of the instability of false confession across oral and written modes revealed significant developmental group effects based on specific mode of confession. The reasons people provided for their choice to confess or not confess were examined and are consistent with cases depicted in the literature of false confessions. Forensic implications, as well as the overlap between this work and that of Steven Jay Lynn are discussed.